The tropical cookbook: Termite diet and phylogenetics—Over geographical origin—Drive the microbiome and functional genetic structure of nests - González Plaza, Juan José; Hradecký, Jaromír (Frontiers in Microbiology, 2023)
Termites are key decomposers of dead plant material involved in organic matter recycling in warm terrestrial ecosystems. Due to a prominent role as urban pests of timber, research efforts have been directed towards biocontrol strategies aimed to use pathogens in their nest. However, one of the most fascinating aspects of termites are their defence strategies that prevent the growth of detrimental microbiological strains on their nests. One of the control factors is the nest allied microbiome. Understanding how allied microbial strains aid termites from pathogen load could provide us with an enhanced repertoire for fighting antimicrobial resistant strains or mine for genes for bioremediation purposes. However, a necessary first step is to characterize these microbial communities. Aiming to gain a deeper understanding of the termite nest microbiome, we carried out a multiomics approach for dissecting the nest microbiome in a wide range of termite species. These cover several feeding habits and three geographical locations at two tropical sides of the Atlantic Ocean, known to host hyper diverse communities. Our experimental approach included untargeted volatile metabolomics, targeted evaluation of volatile naphthalene, taxonomical profile for bacteria and fungi through amplicon sequencing, and further diving into the genetic repertoire through a metagenomic sequencing approach. Naphthalene was present in species belonging to the genera Nasutitermes and Cubitermes. We further assessed the apparent differences in terms of bacterial community structure, having found a stronger influence from feeding habits and phylogenetic relatedness than the geographical location effect. The phylogenetic relatedness among nests’ hosts influences primarily bacterial communities, while diet influences fungi. Lastly, our metagenomic analysis revealed that the gene content provides both soil feeding genera with similar functional profiles, while the wood feeding genus shows a different one. Our results indicate that the nest functional profile is largely influenced by the diet and phylogenetic relatedness, irrespectively of the geographical location.